Insights into magnesium alloy significance - Dipen Kumar Rajak; Akriti Menon (Journal of Alloys and Metallurgical Systems)
Metal alloys are essential materials used in various commercial applications, including automobiles, aeronautics, electronics, and medical devices. Their versatility and durability make them invaluable in industries that require high performance and reliability. In applications such as aero-engineering and automobiles, components are designed to operate on critical principles of withstanding high loads while remaining lightweight. Magnesium alloys are known for their lightweight properties, making them commercially popular for such applications. Mg alloys are categorized into different series, each incorporating different metals. This review article focused on and discussed the thermal and electrical behavior of Mg alloys. Moreover, significant fabrication processes to produce these alloys are also stated and concluded with influencing parameters that provide insights into improving Mg alloys.